2015
DOI: 10.1590/0100-83582015000200020
|View full text |Cite
|
Sign up to set email alerts
|

Imidazolinone Degradation in Soil in Response to Application History

Abstract: -Accelerated herbicide degradation consists in its faster degradation in areas where it has been previously applied, due to the adaptation of microbial population to that particular compound. Accelerated degradation can reduce herbicide persistence and reduce its efficacy in soil. The objective of this study was to investigate if imidazolinone herbicides have enhanced microbial degradation in rice paddy soils. A laboratory experiment was conducted, evaluating the CO 2 evolution rate from soils with and without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 30 publications
2
6
0
2
Order By: Relevance
“…The differences in dissipation rate between the first application and the second one were insignificant for both enantiomers ( Figure S3). The insignificant effect of repeated applications on imazaquin dissipation observed in this study agrees with the results reported by Bundt et al (2015). These authors conducted a non-enantioselective study on the dissipation of five imidazolinone herbicides in soils with a two-year application history and concluded that the prior application of imidazolinones did not stimulate microbial degradation of herbicides from the same chemical group.…”
Section: Dissipation In Unamended Soilssupporting
confidence: 91%
“…The differences in dissipation rate between the first application and the second one were insignificant for both enantiomers ( Figure S3). The insignificant effect of repeated applications on imazaquin dissipation observed in this study agrees with the results reported by Bundt et al (2015). These authors conducted a non-enantioselective study on the dissipation of five imidazolinone herbicides in soils with a two-year application history and concluded that the prior application of imidazolinones did not stimulate microbial degradation of herbicides from the same chemical group.…”
Section: Dissipation In Unamended Soilssupporting
confidence: 91%
“…The proliferation of microorganisms was directly affected by soil moisture [15]. A high soil moisture, with high levels of microbial activity, would stimulate the microbial degradation of imazapic [22,27,28]. Moreover, pesticide adsorption in soil was greater at a low moisture content [29].…”
Section: Resultsmentioning
confidence: 99%
“…Herbicides from the imidazolinone group are effective to control a wide spectrum of weeds; they are used in commercial mixtures, such as imazapyr+imazapic to control red rice, cultivated with the Clearfield ® system. However, the presence of these herbicides in the soil may cause problems to non-tolerant cultures cultivated in succession or rotation (Bundt et al, 2015).…”
Section: Introductionmentioning
confidence: 99%